2021
DOI: 10.22541/au.163828284.40261296/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High resolution species detection: accurate long read eDNA metabarcoding of North Sea fish using Oxford Nanopore sequencing

Abstract: To monitor the effect of nature restoration projects in North Sea ecosystems, accurate and intensive biodiversity assessments are vital. DNA based techniques and especially environmental DNA (eDNA) metabarcoding from seawater is becoming a powerful monitoring tool. However, current approaches are based on genetic target regions of <500 nucleotides, which offer limited taxonomic resolution. This study aims to develop and validate a long read nanopore sequencing method for eDNA that enables improved identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…One poten al solu on may involve employing longer sequences or even full-length genes in eDNA metabarcoding. Novel metabarcoding approaches targe ng en re gene sequences improve dis nc on among similar species (Deiner et al, 2017, Doorenspleet et al, 2021. Future work will evaluate the impact of longer or full-length sequences on classifier performance and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One poten al solu on may involve employing longer sequences or even full-length genes in eDNA metabarcoding. Novel metabarcoding approaches targe ng en re gene sequences improve dis nc on among similar species (Deiner et al, 2017, Doorenspleet et al, 2021. Future work will evaluate the impact of longer or full-length sequences on classifier performance and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several tools for automatic handling of Nanopore amplicon data are available. Examples are NanoRTax (however limited to 16S rRNA amplicons only and intended for taxonomic analysis of microbial community samples, Rodriguez‐Perez et al, 2021) or Decona (for processing data from demultiplexing to consensus calculation, Doorenspleet et al, 2021). However, none of these tools can adequately handle paralogs present in amplified loci.…”
Section: Discussionmentioning
confidence: 99%
“…We benchmark the performance (i.e., the number and taxonomic level of identified zooplankton species) and runtime of PIMENTA with two other existing pipelines, the previous pipeline published by Voorhuijzen-Harink et al [2] as well as Decona [4]. An overview of the procedures, analysis and databases applied in this study is shown in Figure 1.…”
Section: )mentioning
confidence: 99%
“…Metabarcoding data analysis, however, is not yet mainstreamed and many different bioinformatic pipelines have become available over recent years [2,3,4,5,6]. As the sequencing error profile of MinION sequencing differs to that of other sequencing devices such as Illumina sequencers [3,7], analysis pipelines developed with data from other platforms in mind may not perform well on MinION data.…”
Section: Introductionmentioning
confidence: 99%